The Computer Medical Record in Health Screening) ) - COLLEN, M. F.; DAVIS, L. S.; VAN BRUNT, E. E. (Methods of Information in Medicine, 1971)
Computerized data banks require very complex patient record files. Our method of storing medical data from a multiphasic health screening program is described in detail, induding the mechanics for providing on-line medical record linkage.
Keywords: Computer Medical Record; Multiphasic Screening; Record Linkage; Data Base